Samuel Beckett and Édith Fournier Translating the 'Untranslatable' Worstward Ho. Issue 2 (September 2017) - Cordingley, Anthony
Abstract : Worstward Ho is renowned for being Beckett's only text that he deemed untranslatable. However, fragments of a translation by him of Worstward Ho into French recently discovered in the archives of Les Éditions de Minuit at the Institut mémoires de l'édition contemporaine reveal that his work on this translation was more assiduous than he led others to believe. In this article, I compare the published French translation of the text by Édith Fournier with these newly discovered fragments of Beckett's translation. Remarkable similarities between the two translations are observed, and the hypothesis that there was a degree of collaboration on the French translation between the two friends is here tested.